Effective investigation of extracted conditions to obtained mogroside content from Siraitia grosvenorii - Son, Pham Huong; Tuan, Hoang Van; Hien, Nguyen Thi; Oanh, Le Kieu (Academia Journal of Biology, 2013)
Siraitia grosvenorii extract and its igredients, especially mogroside, were widely used as a food additive and many other applications in pharmaceutial industry. The purpose of this study is to determine the effect of extraction conditions to mogroside content in S. grosvenorii extract. The results showed that the osmotic pressure at the different concentration of solvent affects to obtained mogroside content. Increasing temperature can accelerate the diffuse velocity of mogroside into solvent. By using the method of fractional soaking extraction with 55% ethanol solvent at 60oC temperature in 70 minutes, and rate of biomass/solvent is 1:19 (g/ml) the highest mogroside was obtained, and in this case the percentage of obtained mogroside is determined at 76.4%.